CHEMICAL PROFILE OF TINFOIL BARB (Barbonymus schwanenfeldii) WITH DIFFERENT PROCESSING - Muhammad ArifSatrio Hutomo; Merry Sukmiwati; Dewita Dewita (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTThe purpose of this study was to determine the chemical profile and fatty acids contained by tinfoil barb(Barbonymus schwanenfeldii) with grilled and steamed processing. The analysis parameters were chemical and fatty acid analysis. Based on chemicalanalysis the grilled tinfoil barbcontained of water 67.85%, ash 2.15%, protein 17,84%, fat 6.13% with 9 of fatty acids consisted of 6 saturated fatty acidsnamely caprylic (not detected), caproic (not detected), lauric (0,33%), myristic (0,60%), palmitic (17,79%), and stearic acid (2,61%), 1 of monounsaturated fatty acid namely oleic (25,82%),and 2 ofpolyunsaturated fatty acid namelylinoleic(34,58%) and linolenic acids (16,64%). Meanwhile, the steamed tinfoil barb containedwater (69.01%), ash (1.89%), protein 17,06%,and fat 7.99% with 9 of fatty acids consisted of 6 saturated fatty acids namely caprylic (not detected), caproic (0.05%), lauric (2,06%), myristic (1.88%), palmitic (24.65%) and stearic acid (4.05%);1 of monounsaturated fatty acid namely oleic (28,99%), and 2 of polyunsaturated fatty acids namely linoleic (21,62%) and linolenic acid(15,12%).Keywords: tinfoil barb, chemical profile, grilled, steamed, fatty acid